Software Design Tool for Sizing PV Stand-Alone System and Hybrid PV-Diesel System with Iraq Climate - Hashim, Saja Majeed; Abdulateef, Osamah Fadhil; Alattar, Falah Ibrahim (Al-Nahrain Journal for Engineering Sciences, 2019)
This paper displays the improvement of Graphical User Interface programming for sizing principle segment in Stand-Alone PV system and PV- Diesel hybrid power system based on Iraq conditions. The solar system software is a tool depends on the input data by the user to give correct results on the basis of what has been introduced. Therefore, this software tool Includes products (PV modules, charge controller, inverter, battery and diesel generator) which can be obtained from the market with their detail. This software presents a guideline for photovoltaic system integrator to match the load requirement to design the effective size of components and system configuration, in hybrid PV–Diesel system. The ratio of photovoltaic solar energy to diesel generators is introduced by considering the contribution of hybrid system energy.